2008
DOI: 10.1111/j.1460-2466.2008.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Race in Police-Civilian Interactions: A Content Analysis of Videotaped Interactions Taken During Cincinnati Police Traffic Stops

Abstract: Although the study of police-civilian relations has recently entered the intergroup communication arena, there are no studies of actual interactions between these social categories. In part to rectify that stark omission and guided by communication accommodation theory, 313 randomly sampled video recordings from police cars on traffic stops in Cincinnati, Ohio were content analyzed. The study revealed 3 key differences as a function of the officers' and drivers' races: (a) Black drivers were more likely to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 25 publications
(39 reference statements)
0
51
0
Order By: Relevance
“…The present study builds upon Dixon, Schell, Giles, and Drogos (2008) who invoked CAT to examine police脕civilian interactions. Focusing on African American and White police and civilians, the researchers conducted a content analysis of a stratified random sample of videorecorded traffic stops received from the Cincinnati Police Department.…”
Section: Theoretical Framework and Relevant Studiesmentioning
confidence: 99%
“…The present study builds upon Dixon, Schell, Giles, and Drogos (2008) who invoked CAT to examine police脕civilian interactions. Focusing on African American and White police and civilians, the researchers conducted a content analysis of a stratified random sample of videorecorded traffic stops received from the Cincinnati Police Department.…”
Section: Theoretical Framework and Relevant Studiesmentioning
confidence: 99%
“…To our knowledge only one previous effort has been made to conduct "armchair" observation of police by using video recordings of police-citizen encounters, rather than conducting in-person observation, to collect systematic information about police actions for analytical purposes (Dixon et al 2008). That study focused on traffic stops only, and in addition, it was designed to examine the influences of citizen and police officer race on communication patterns, and particularly "communication accommodation"; it did not extend to the wide range of citizen and officer behaviors on which SSO of police has dwelled, or on procedural justice as such.…”
Section: Schenectady Observationsmentioning
confidence: 99%
“…(In re Cincinnati Policing 2003, 7) Both agreements were overseen by the same court-appointed monitor, though the collaborative agreement also provided for the selection of an independent evaluator. The RAND Corporation was selected and, among other things, conducted two surveys of the community-one in 2005 and a second in 2008-and also analyzed police-citizen interactions in annual samples of traffic stops across four years by coding the audio and video recordings captured by CPD's in-car cameras (Ridgeway et al 2009; also see Dixon et al 2008).…”
Section: Implications For Police Reformmentioning
confidence: 99%
“…For instance, a content analysis of traffic stops in a metropolitan city in the Midwest showed that Blacks (vs. Whites) were more likely (often 3-5 times as much) to be searched, to be asked whether they had weapons, to be asked to leave the vehicle, or to have a passenger and/or vehicle searched (Dixon, Schell, Giles, & Drogos, 2008). In addition, in an analysis of traffic violations in a large metropolitan county in the Southeast, Alpert, Dunham, and Smith (2007) found that officers were significantly more likely to conduct a background check, complete a field interview card, and conduct pat-down and vehicle searches when they stopped Black motorists compared with White motorists.…”
Section: Racial Profilingmentioning
confidence: 99%